Development of KKNI Oriented Learning Devices Assisted by the Synectic Model - Charles Kapile; Nuraedah Nuraedah (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to produce KKNI-oriented learning tools assisted by the Synectic Model in the Indonesian society studies course, a university in Indonesia's history education program. This research was carried out in the sixth semester using Educational Research which was adapted from the development model according to Borg Gall, which consisted of six stages: a preliminary study, planning stage, and drafting stage for learning device products KKNI-oriented, assisted by a synectic model, the product validation stage, the revision stage, and product testing, as well as the dissemination stage. The trial subjects of the KKNI-oriented learning device assisted by the Synectic model in the Indonesian society study course were 43 students in that study program. The results of the research are: (1) KKNI-oriented learning tools assisted by a synectic model of Indonesian society studies courses have been produced in a very good category based on the results of product validation by four expert lecturers and the results of student response questionnaires, and (2) KKNI-oriented learning devices assisted by Synectic models in Indonesian society studies courses are effectively used in learning, especially to train students’ creative thinking skills.